2015
DOI: 10.1293/tox.2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

A spontaneously occurring malignant pituicytoma in a male sprague dawley rat

Abstract: Pituicytoma is an extremely rare neoplasm derived from pituicytes, which are glial cells in the posterior lobe of the pituitary gland. A malignant pituicytoma was found in the intracranial cavity of a 55-week-old male Sprague-Dawley rat. Macroscopically, the tumor was located on the sphenoid bone and involved the pituitary gland. The tumor was composed of sheets of fusiform cells with spindle- or pleomorphic-shaped nuclei and abundant eosinophilic cytoplasms. The cells were arranged in a whirling or irregular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In conclusion, malignant craniopharyngioma should be considered a differential diagnosis in the rat when a tumor with stratified squamous epithelial features and locally aggressive growth pattern is revealed in the sellar or suprasellar region. The present case of a malignant craniopharyngioma extends further the spectrum of malignant pituitary tumors in the rat 24 , 25 .…”
supporting
confidence: 59%
“…In conclusion, malignant craniopharyngioma should be considered a differential diagnosis in the rat when a tumor with stratified squamous epithelial features and locally aggressive growth pattern is revealed in the sellar or suprasellar region. The present case of a malignant craniopharyngioma extends further the spectrum of malignant pituitary tumors in the rat 24 , 25 .…”
supporting
confidence: 59%
“…Anti-GFAP IHC (H); note the strongly positive cytoplasmic staining. Images 5E, 5F, 5G and 5H were reproduced with permission from Moroki et al, 2015.…”
Section: Figurementioning
confidence: 99%
“…Pituicytes are modified astrocytes of the pars nervosa that help to regulate the storage and secretion of antidiuretic hormone and oxytocin (Hatton 1988). By definition, neoplasms of these specialized cells are called pituicytomas and they have been reported rarely in mice, rats, cats, dogs, and primates, including humans (Tekeli, Morton, and Cusick 1997;Satoh et al 2000;Moroki et al 2015;Zaki et al 1975;HogenEsch, Broerse, and Zurcher 1992;Figarella-Branger et al 2002). In the rat, they are typically low-grade neoplasms, although local invasion is often present.…”
Section: Intracranial Conundrums Imentioning
confidence: 99%
“…In rats, the frequency increases with age in all strains, and the tumors usually begin to appear between 13 and 24 months of age 6 . Primary proliferative lesions of the pituitary are, as is well known, most frequently found in the pars distalis and are rarely encountered in the pars intermedia or pars nervosa 20 , 21 , 22 , 23 . Immunohistochemical studies confirmed that most pituitary tumors are PRL positive 24 , 25 , 26 .…”
mentioning
confidence: 94%